The Elements for Sustainable E-Business Modelling: A 3D Approach - Dewan, Mohammed Naim Ahmed; Chowdhury Md. Maruf Hossan; Quaddus, Mohammed (PACIS, 2012)
The sustainability of the business is a global contemporary issue. E-business modelling is another already established term as it converts technology into economic value. Although e-business modelling and sustainability of the business are the two significant global trends now but still there is no common perception about the elements that are essential for a sustainable e-business model. Surprisingly, none of the approaches even consider sustainability as a major element while modelling e-business. Therefore, after completing extensive literature review on e-business modelling and sustainability of the business we carefully identify and determine the required elements for a sustainable e-business model in this paper. We also clarify the significance for selecting these elements. The elements are three dimensional (3D) and selected from customer value area, business value area, and process value area so that the modelling elements preserve the interests of all stakeholders while upholding the sustainability.